Essential health services during COVID-19: an unidentified lead - Jose, Hannah; Pathak, Vineet Kumar (International Journal of Research in Medical Sciences, 2020)
The struggle against COVID-19, which once started as an amicable endeavor with an anticipated climax has now turned into an unending, mysterious puzzle with lesser hope. What impacts more is the deficiency of financial backups in the health sector, for such an unexpectedly long duration. All these are pointing us towards a more sustainable, cost-effective method to fight against COVID-19, where the daily health and lifestyle of people are also considered. Maintenance of provision of essential health care services is important and urgent since this is the only way to decrease the indirect morbidity and mortality from other health conditions, thereby preventing the health system from collapse. Various new reforms have been made in health policies of different vulnerable groups including, people living with chronic diseases, the elderly, children and mothers, and pregnant women. To avoid the re-emergence of vaccine-preventable diseases and also future similar contagious diseases, reforms are also made in immunization services. Implementation of these amendments in the health care sector is a need of the hour and it demands a broader perspective with a long-term goal. Further, identifying gaps for innovative initiatives in the same direction are also to be welcomed, for a sustainable post-COVID-19 phase.